Analysis of the Effect of Price and Quality on Repurchase Intention through Customer Satisfaction on Imported Vegetables in Batam - Alicia, Angelina; Laulita, Nasar Buntu (Jurnal Maksipreneur, 2024)
This study examines the repurchase intention of imported vegetables in Batam City by analyzing consumer satisfaction, price, and quality as factors influencing repurchase intentions. Path analysis with SmartPLS was used to test the hypothesis. The sample used in this study was 199 respondents. The results showed a positive relationship between customer satisfaction and repurchase intention, there was no relationship between price and repurchase intention and showed that quality was positively related to repurchase intention. The results also show that there is a significant influence between quality on repurchase intentions through customer satisfaction. However, customer satisfaction failed to mediate the relationship between price and repurchase intention.